Du concept au cosmos : perspectivisme chez Bill Vazan - Bérard, Serge (Ciel variable)

(untitled) (Les Productions Ciel variable, 2007)
Since the end of the 1960s, Bill Vazan has been producing conceptual works in the form of urban itineraries for which he uses various modes of transportation (walking, driving, riding buses or subways). These performative endeavours result in photographic series accompanied by various written records and sketches that document his actions. The photographs always imitate the characteristics of amateur photography: imperfect cropping, reflections, unwanted interferences, and indifference to lighting conditions. This approach renders visible time and space as lived during the artist's travels. In their texts, Serge Bérard and Henry Lehman discuss the ramifications of Vazan's land art and photographic projects.